2014
DOI: 10.1074/jbc.m114.569624
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Fluorescence Labeling Reveals a Revised N-terminal Membrane Topology and Functional Periplasmic Residues in the Escherichia coli Cell Division Protein FtsK

Abstract: Background:FtsK is an essential membrane protein that links chromosome segregation and cell division in bacteria. Results: A revised membrane topology of FtsK highlights a large functional periplasmic loop. Conclusion: Key residues in the newly identified periplasmic loop of FtsK couple division of the cytoplasmic and outer membranes. Significance: FtsK functions as a critical checkpoint for the transition between cell growth and septation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 68 publications
4
27
0
Order By: Relevance
“…Since the deletion of SftA and that of a Walker A mutant have the same phenotype [Kaimer et al, 2009], we suggest that the Nterminal part of SftA has no intrinsic function other than mid-cell targeting. This is in contrast to E. coli FtsK, in which a mutation within a loop in the N-terminus resulted in uncoupling invagination of the inner and outer membranes [Berezuk et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Since the deletion of SftA and that of a Walker A mutant have the same phenotype [Kaimer et al, 2009], we suggest that the Nterminal part of SftA has no intrinsic function other than mid-cell targeting. This is in contrast to E. coli FtsK, in which a mutation within a loop in the N-terminus resulted in uncoupling invagination of the inner and outer membranes [Berezuk et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The filaments are then tethered to the membrane, forming the Z-ring. They act as the scaffold for divisome assembly and provide the driving force for cell constriction (7)(8)(9)(10). Although the localization of FtsZ filaments and the requirement for recruiting other divisome proteins is well established, the organization and dynamics of the Z-ring have yet to be fully described.…”
mentioning
confidence: 99%
“…In both Bdellovibrios, there is an Na + -transporting, K + -dependent pyrophosphatase (TC 3.A.10). Also, a cell division protein, FtsK (TC 3.A.12) of known topology [Berezuk et al 2014], can be found in both.…”
Section: Resultsmentioning
confidence: 99%